The evaluation of a multi-modal cognitive-behavioural approach to treating an adolescent with conduct disorder - Mashalaba, Eugenia Dudu (Rhodes University, Faculty of Humanities, Department of Psychology, 2005)
Conduct Disorder (CD) is a repetitive and persistent pattern of behaviour in which the basic rights of others or major age-appropriate societal norms or rules are violated. It is one of the most common problems in South African schools, particularly in those that are poverty-stricken. The child who participated in the study lived in the shelter that was for homeless and disadvantaged children. He attended at Amasango School where the majority of children in the shelter attended. There were many conduct-disordered children in the shelter and the school, particularly in the school. They disrupted classes making in difficult for teachers to carry out their education activities. The aim of this study was to draw on the standard procedures of the CBT in order to design interventions that would be effective in reducing aggressive behaviour in an adolescent who had CD Adolescent-Type and who lived at the shelter. This case study evaluated the effectiveness of a multi-modal CBT programme in a 16 year-old Black male who had been displaying aggressive behaviour for about a year. The treatment consisted of 23 sessions and included teacher counseling, contingency management, self-control and self-instructional training. The treatment was evaluated qualitatively by means of interviews with the child and teacher and quantitatively by means of repeated applications of behaviour checklists completed by the teacher. The results showed a decrease in the client's aggressive behaviour and an increase in prosocial behaviour. The client ultimately ceased from all aggressive behaviour towards his peers and this outcome was sustained during his last two months in therapy.
Keywords: Conduct disorders in adolescence; Aggressiveness in adolescence; Violence in children; Behavior disorders in children -- Treatment; Attention-deficit disorder in adolescence; Oppositional defiant disorder in adolescence; Cognitive therapy Case studies